2013
DOI: 10.7554/elife.00105
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells loaded with FK506 kill T cells in an antigen-specific manner and prevent autoimmunity in vivo

Abstract: FK506 (Tacrolimus) is a potent inhibitor of calcineurin that blocks IL2 production and is widely used to prevent transplant rejection and treat autoimmunity. FK506 treatment of dendritic cells (FKDC) limits their capacity to stimulate T cell responses. FK506 does not prevent DC survival, maturation, or costimulatory molecule expression, suggesting that the limited capacity of FKDC to stimulate T cells may be due to inhibition of calcineurin signaling in the DC. Instead, we demonstrate that DC inhibit T cells b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…FK506 (tacrolimus) binds to the same cellular target protein (FKBP12) as does rapamycin but acts through a different downstream mechanism [27]. Orange et al [28] have reported that FK506 is adsorbed rapidly and then released by dendritic cells in a manner analogous to our observations for rapamycin. Figure 3.…”
Section: Other Isds Can Increase the Potency Of Mscssupporting
confidence: 64%
See 1 more Smart Citation
“…FK506 (tacrolimus) binds to the same cellular target protein (FKBP12) as does rapamycin but acts through a different downstream mechanism [27]. Orange et al [28] have reported that FK506 is adsorbed rapidly and then released by dendritic cells in a manner analogous to our observations for rapamycin. Figure 3.…”
Section: Other Isds Can Increase the Potency Of Mscssupporting
confidence: 64%
“…There are precedents for the loading of cells with hydrophobic drugs, with Pessina et al [35] reporting that sufficient amounts of the anti-cancer drug paclitaxel were adsorbed by MSCs in a 24-h incubation to reduce tumor growth in vivo and Orange et al [28] finding that FK-506eloaded dendritic cells could inhibit autoimmune arthritis. A rapid partition of ISDs into cells would appear to explain our observations of increased suppression by brief pretreatments of MSCs, fibroblasts, APCs and HUVECs and may explain at least part of the increased suppression reported for rapamycintreated endothelia and Tregs [30,36].…”
Section: Discussionmentioning
confidence: 98%
“…As shown on the simulation studies (in Supplementary Material available online at http://dx.doi.org/10.1155/2016/4680642), the permutation-based test provides a valid means for testing the difference of two curves, achieving the desired type I error rate. We applied this procedure to longitudinal data collected by Orange et al [21] and showed that the results obtained were consistent with those obtained by using a generalized estimating equation model [22, 23]. Therefore, the proposed procedure to test the difference between curves using LPS can be employed in a wide range of applications in longitudinal data analysis.…”
Section: Resultssupporting
confidence: 67%
“…Although the inhibition of calcineurin activity in T cells is a known effect of FK506, additional intracellular targets such as p38 and c‐Jun N‐terminal kinase have been suggested 33. Interestingly, our laboratory has recently shown that FK506 preferentially accumulates in DCs, thereby targeting T cells engaged in antigen‐specific T cell–APC interactions 34. It is possible that FK506 may similarly act upon APCs in the brain.…”
Section: Discussionmentioning
confidence: 99%